A proof‐of‐concept pilot randomized comparative trial of brief Internet‐based compassionate mind training and cognitive‐behavioral therapy for perinatal and intending to become pregnant women. (23rd February 2018) - Kelman, Alex R.; Evare, Benjamin S.; Barrera, Alinne Z.; Muñoz, Ricardo F.; Gilbert, Paul
Abstract : Objective: Depression is a prevalent and costly mental health problem that affects women as well as their larger communities, with substantial impacts on mother and infant during childbearing years. Face‐to‐face care has not adequately addressed this global concern due to difficulties in scaling these resources. Internet interventions, which can provide psychological tools to those lacking adequate access, show promise in filling this void. Method: We conducted a 2‐condition proof‐of‐concept pilot randomized trial comparing brief Internet‐based cognitive behavioural therapy (CBT) and brief Internet‐based compassionate mind training (CMT) for women who are currently pregnant, became pregnant within the last year, and intend to become pregnant in the future. Results: We found that, although CMT and CBT demonstrated near equivalence in improving affect, self‐reassurance, self‐criticism, and self‐compassion, CMT showed superiority to CBT in reducing depression and anxiety symptoms. Conclusion: These findings provide a compelling initial argument for the use of CMT as an avenue for addressing problems associated with negative affect. Implications, limitations, and future directions along this line of research will also be discussed.